The Effect of Service Quality, Price, and Brand Image on Purchasing Desicions of Moslem Wedding Equipment Service - Badik Anna Baroroh; J.E. Sutanto (Universitas Ciputra Surabaya, 2021)
Moslem Wedding Organizer is a form that personally helps brides and families to providing the supplies and implementation of wedding events in accordance with Islamic religious rules. The population of Surabaya city is majority moslem city that still adhering to diverse traditions and cultures, this is an opportunity for krar Suci to become the choice of moslem wedding organizer for brides in Surabaya. Several factors that are considered by the brides in making decisions about choosing wedding organizer are service quality, price, and brand image, so this study aims to determine the effect of service quality, price and brand image on the decision to purchase moslem wedding equipment. This type of research is quantitative, with the population being all Muslim couples in Surabaya who married in 2019, at the age of 19, who used the services by a wedding organizer. The sampling technique used incidental sampling with a sample size of 100 respondents who were processed using multiple linear regression analysis. The results of this study indicate that there is a positive and significant effect partially and simultaneously on service quality, price, and brand image on purchasing decisions for moslem wedding equipment services. Suggestions for the company are to improve service quality, re-analyze prices according to market, and improve brand image to be better known and trusted by the public.